2017
DOI: 10.1016/j.wasman.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different approaches for the estimation of odour emissions from landfill surfaces

Abstract: The aim of this study is related to the assessment of odour emissions from landfill surfaces. Up to now, there is not a widely accepted method to quantify odour emissions from this particular kind of source. Five different methods were developed and investigated. These methods can be considered as based on three distinct approaches, both experimental and computational. The first approach provides to use models for the estimation the landfill gas production, whereby the second and the third approach are based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Odour Emission Factors (OEFs) are useful tools as they are not only descriptive indicators but also predictive, in agreement with the research performed in an environmental field that brought about the development of OEFs for different kinds of industrial plants such as: wastewater treatment plant (WWTP), Municipal Solid Waste Management Plant (MSWMP), animal rendering plants, and landfills [70,71,72,73,74,75,76,77]. …”
Section: Methodssupporting
confidence: 55%
“…Odour Emission Factors (OEFs) are useful tools as they are not only descriptive indicators but also predictive, in agreement with the research performed in an environmental field that brought about the development of OEFs for different kinds of industrial plants such as: wastewater treatment plant (WWTP), Municipal Solid Waste Management Plant (MSWMP), animal rendering plants, and landfills [70,71,72,73,74,75,76,77]. …”
Section: Methodssupporting
confidence: 55%
“…The difference between odor concentrations in the samples obtained through both Lindvall and static chambers from the present studies are summarized in Table 4. Lucernoni et al (2017) compared the odor emission rates achieved by wind tunnel and flux chamber and reported that measurements carried out with wind tunnel gave emission value of 248,050 ou E /sec, whereas with flux chamber it was 6150 ou E /sec. Parker et al (2013) compared the sampling methods of collecting the following five compounds from the surface source: phenol, 4-methylphenol, 4-ethylphenol, indole, and skatole.…”
Section: Discussionmentioning
confidence: 99%
“…Emission of odorous gases from mixed land use patterns along with landfill in the cities have resulted in nuisance and other problems associated with the setting up of waste treatment facilities in and around cities as studied and documented [2]; [13]; [15]; [19]; [21]; [22]; [26]; [27]; [32]; [34]; [35]; [37]. Odour can be expressed as the "perception of smell" or in scientific terms, "a sensation resulting from the reception of stimulus by the olfactory sensory system" [12].…”
Section: Introductionmentioning
confidence: 99%